Application of dynamic current density for increased concentration factors and reduced energy consumption for concentrating ammonium by electrodialysis. (15th October 2019) - van Linden, Niels; Spanjers, Henri; van Lier, Jules B.
Abstract: Ammonium (NH4 + ) can be recovered from water for fertiliser production or even energy production purposes. Because NH4 + recovery is more effective at increased concentrations, electrodialysis (ED) can be used to concentrate NH4 + from side streams, such as sludge reject water, and simultaneously achieve high NH4 + removal efficiencies. However, the effect of osmosis and back-diffusion increases when the NH4 + concentration gradient between the diluate and the concentrate stream increases, resulting in a limitation of the concentration factor and an increase in energy consumption for NH4 + removal. In this study, we showed that operation at dynamic current density (DCD) reduced the effect of osmosis and back-diffusion, due to a 75% decrease of the operational run time, compared to operation at a fixed current density (FCD). The concentration factor increased from 4.5 for an FCD to 6.7 for DCD, while the energy consumption of 90% NH4 + removal from synthetic sludge reject water at DCD remained stable at 5.4 MJ·kg-N −1 . Graphical abstract: Image 1 Highlights: Osmosis limited the concentration factor to 4.5 using a fixed current density (CD). Back-diffusion increased the energy consumption using a fixed CD. Operational run time for 90% NH4 + removal was reduced by 75% using dynamic CD. At dynamic CD osmosis decreased, leading to an increase of the concentration factor of 6.7. At dynamic CD back-diffusion decreased, leading to a stable energy consumption of 5.4 MJ·kg-N −1 .